Perencanaan Desain Tebal Perkerasan Jalan Lentur (Flexible Pavement) Untuk Mendukung Tingkat Pelayanan Jalan di Kampus Politeknik Negeri Lampung - Titi Ariyanti; Mira Wisman; Resti Agustina; Andy Eka Saputra; Rahayu Putri Amalia (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The availability of reliable road infrastructure is an important factor in supporting transportation and mobility activities in educational areas. Campus roads as supporting infrastructure for academic activities are required to be able to provide an optimal level of service along with the increasing volume and traffic load. The increase in traffic load on the campus roads of the Politeknik Negeri Lampung has not been balanced by adequate road infrastructure conditions. Therefore, this study aims to conduct a case study of flexible pavement thickness design planning to support the improvement of road service levels on the Politeknik Negeri Lampung. This study was conducted on the Main Road of the Lampung State Polytechnic with the survey being carried out from Monday to Thursday for 6 hours/day. The analysis results show that the recommended flexible pavement structure design based on the 2024 MDPJ for a design life of 20 years is a 60 mm thick AC-WC, a 200 mm thick Class A Aggregate Foundation Layer, and a 150 mm thick Class B Aggregate Foundation Layer, with a degree of saturation (DJ) value of 0.345 in the stable flow category, but vehicle speeds are starting to decrease.